Does study subject diversity influence cardiology research site performance?: Insights from 2 U.S. National Coronary Stent Registries - Batchelor, Wayne B.; Damluji, Abdulla A.; Yong, Celina; Fiuzat, Mona; Barnett, Scott D.; Kandzari, David E.; Sherwood, Matthew W.; Epps, Kelly C.; Tehrani, Behnam N.; Allocco, Dominic J.; Meredith, Ian T.; Lindenfeld, JoAnn; et al. (The American heart journal, 2021)
Minorities and women are underrepresented in cardiovascular research. Whether their higher enrollment can be predicted or influences research site performance is unclear. We evaluated 104 sites that enrolled 4,184 patients in the U.S. Platinum Diversity (PD) and Promus Element Plus (PE Plus) studies (2012 to 2016). Research sites were ranked from lowest to highest minority and female enrollment, respectively. United States Census Bureau division and core-based statistical area (CBSA) populations were determined for each site and the following study performance metrics compared across quartiles of minority and female enrollment, respectively: (1) study subject enrollment rate (SER), (2) time to first patient enrolled, (3) rate of follow-up visits not done, (4) rate of follow-up visits out of window, and (5) protocol deviation rate (PDR). Multivariable regression was used to predict SER and PDR. Minority enrollment varied by region (P = .025) and population (P = .024) with highest recruitment noted in the Pacific, West South Central, South Atlantic, Mid-Atlantic and East North Central divisions. Female enrollment bore no relationship to region (P = .67) or population (P = .40). Median SER was similar in sites withi the highest vs lowest quartile of minority enrollment (SER of 4 vs 5 patients per month, respectively, P =0.78) and highest vs. lowest female enrollment (SER of 4 vs 4, respectively, P = .21). Median PDR was lower in sites within the highest vs lowest minority enrollment (0.23 vs 0.50 PDs per patient per month, respectively, P = .01) and highest vs. lowest female enrollment (0.28 vs. 0.37 PDs per patient per month, respectively, P = .04). However, this relationship did not persist after multivariable adjustment. All other site performance metrics were comparable across quartiles of minority and female enrollment. Minority, but not female enrollment, correlated with research site geographic region and surrounding population. High enrollment of minorities and women did not influence study performance metrics. These findings help inform future strategies aimed at increasing clinical trial diversity. The PD and PE Plus studies are registered at www.clinicaltrials.gov under identifiers NCT02240810 and NCT01589978, respectively. Question: Does the enrollment of more Blacks, Hispanics and women in US cardiovascular research studies influence the overall rate of study subject enrollment and/or other key study site performance metrics and can diverse enrollment be predicted? Findings: In this pooled analysis of 104 sites that enrolled 4,184 patients in the Platinum Diversity and Promus Element Plus Post-Approval Studies, we found that the enrollment of higher proportions of underrepresented minorities and women was univariately associated with lower protocol deviation rates while having no effect on other site performance metrics. A site's geographic location and surrounding population predicted minority, but not female enrollment. Meaning: These findings suggest that cardiovascular research subject diversity may be predicted from site characteristics and enhanced without compromising key study performance metrics. These insights help inform future strategies aimed at improving clinical trial diversity.